PERILAKU HARIAN DAN PREFERENSI MAKAN LEMUR EKOR CINCIN (Lemur catta) DI BALI ZOO, GIANYAR - ., Stefanny; Yuni, Luh Putu Eswaryanti Kusuma; Ginantra, I Ketut (SIMBIOSIS, 2023)
Ring-tailed lemurs ( Lemur catta ) is a primate that live in Madagascar.  Poor habitat quality, limited land area, severe forest fragmentation causes a decrease in the availability of food sources for ring-tailed lemurs in nature so that the ring-tailed lemur population is increasingly threatened. Conservation effort was carried out on ring-tailed lemurs ( Lemur catta ) outside their natural habitat. One of the conservation institutions in Bali is the Bali Zoo. This study aims to observe the daily behavior and eating preferences of ring tailed lemur ( Lemur catta ) at Bali Zoo. This research was conducted on seven ring-tailed lemur at Bali Zoo in January-February 2022 and was carried out at 08.00 am – 04.00 pm. The observation method used was the focal animal sampling and the recording was carried out by the instantaneous recording method with an interval of 30 seconds for 30 minutes. The data obtained were analyzed by using Microsoft excel to calculate the daily behavior formulas, and later was described in a comparative descriptive way. The most frequent behavior were resting (resting) 40.97%. The most preferred food for ring-tailed lemur was grapes Vitis vinifera (16.77%). This research provides data and information from the study species in order to help  to improve the management of ex-situ conservation.